A simple but powerful simulated certainty equivalent approximation method for dynamic stochastic problems - Yongyang Cai; L. Judd Kenneth (Quantitative Economics, 2023)
We introduce a novel simulated certainty equivalent approximation (SCEQ) method for solving dynamic stochastic problems. Our examples show that SCEQ can quickly solve high-dimensional finite- or infinite-horizon, stationary or non- stationary dynamic stochastic problems with hundreds of state variables, a wide state space, and occasionally binding constraints. With the SCEQ method, a desk- top computer will suffice for large problems, but it can also use parallel tools ef- ficiently. The SCEQ method is simple, stable, and can utilize any solver, making it suitable for solving complex economic problems that cannot be solved by other algorithms.
Keywords: C61; C63; C68; Q54; Q58; 330; Stochastic dynamic programming; competitive equilibrium; large- scale model; integrated assessment model; new Keynesian model; zero lower bound; occasionally binding constraint; nonstationary problem; parallelism